과도안정도 해석을 위한 지능형 부하모델의 새로운 접근법 - 李鍾弼(Jong-Pil Lee); 林裁尹(Jae-Yoon Lim); 池平植(Pyeong-Shik Ji) (전기학회 논문지 P권, 57(2), 2008)
The field of load modeling has attracted the attention since it plays an important role for improving the accuracy of stability analysis and power flow estimation. Also, load modeling is an essential factor in the simulation and evaluation of power system performance. However, conventional load modeling techniques have some limitations with respect to accuracy for nonlinear and composite loads. Thus, precision load modeling technique and reasonable application method is needed for more accurate power system analysis. In this paper, we develop an intelligent load modeling method based. on neural network and application techniques for power system. The proposed method makes it possible to effectively estimate the load model for nonlinear models as well as linear models. Reasonable application method is also proposed for stability analysis. To demonstrate the validity of the proposed method, various experiments are performed and their results are presented.